Genomic and functional profiles of two Antarctic chitin-degrading Arthrobacter strains - Yesenia M. Santa-Cruz Vasquez; Luis Gabriel Cueva-Yesquen; Luiz Henrique Rosa; Alysson Wagner Fernandes Duarte; Valéria Maia de Oliveira (Extremophiles, 2026)
Chitin is the second most abundant polysaccharide in nature and constitutes a key structural component in the cell wall of fungi and invertebrate exoskeletons. Chitinases produced by Antarctic organisms have demonstrated high catalytic efficiency, being promising tools for sustainable biotechnological processes. Therefore, the objective of this study was to identify the genes responsible for chitin degradation in the genomes of two Antarctic Arthrobacter strains, as well as to evaluate their biotechnological potential. Whole-genome sequencing followed by phylogenomic analysis revealed that both strains 492 and 285 belong to the species Arthrobacter psychrochitiniphilus. Genome assembly and annotation confirmed the genetic potential for chitinase production, showing that both bacteria possess the gene encoding type C chitinase (Chi C) from the GH18 family. Genomic comparative analysis revealed that they possess a total of eleven genes related to glycoside hydrolases (GH) and carbohydrate-binding modules (CBM), highlighting GH13 and GH65. Arthrobacter psychrochitiniphilus 492 was classified as psychrophilic, while A. psychrochitiniphilus 285 was classified as mesophilic-psychrotolerant. The enzyme production by A. psychrochitiniphilus 285 was 19.9 U/L, in 96 h at 15 °C, and the chitinase showed activity against the Aspergillus sp. series nigri CBMAI 1846, indicating promising potential for the formulation of bioinoculants and sustainable agriculture.